Citocinas e proteínas de fase aguda do soro como marcadores de regressão da resposta inflamatória pelo tratamento, na tuberculose pulmonar - Peresi, Eliana [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
A tuberculose é uma doença ainda em expansão, que foi declarada pela Organização Mundial da Saúde, em 1995, emergência sanitária mundial. Dificultam seu controle a longa duração do tratamento e ausência de marcadores para medir o sucesso ou a falha deste tratamento. Na patogenia da tuberculose, citocinas como IFN-γ e TNF-α tem papel fundamental, pois são responsáveis pela interação do linfócito T com o macrófago infectado, fator central da imunidade protetora contra o M. tuberculosis, sendo também produzidas durante essa interação. Como as citocinas pró-inflamatórias...

Tuberculosis is still increasing and was declared a worldwide sanitary emergency by the WHO in 1995. Its control is difficult due to long treatment duration and lack of markers of treatment success or failure. Cytokines such as IFN-y and TNF-a., a central factor in immune response against M. tuberculosis, are responsible for the interaction between T Iymphocytes and the infected macrophage, and are also produced during this interaction. As proinflammatory cytokines have a close relationship with micobacteria clearance, in fact even preceding it, they could be used as markers for inflammatory activity and response to treatment. Proinflammatory cytokines act in the liver and stimulate a strong local and systemic acute phase response (APR) as a result of homeostatic and physiological responses also induced by them. Acute phase proteins produced by cytokine activity are useful diagnostic markers that could also be used to monitor treatment response as they can be serially quantified. The objective of this study was to evaluate IFN-y, TNF-a, IL-10, and TGF-13 production in supernatant of peripheral blood mononuclear cells (PBMC) and monocytes (MO) cultures, and the serum acute phase response through total protein, albumin, globulins, C-reactive protein (CRP), a-1-acid glycoprotein (AGP), and erythrocyte sedimentation rate (ESR) as regression markers of inflammatory response during pulmonary tuberculosis treatment. Twenty blood donors (G1) from the Blood Bank at Botucatu School of Medicine's University Hospital (HC-FMB) were evaluated once and 28 (G2) pulmonary tuberculosis patients: 13 from HC-FMB and 15 from the Bauru State Health Secretary. Patients were evaluated at three moments of treatment: before (M1), at three months (M2), and at the end (M3). Cytokines were determined in 20mL of peripheral blood (ELlSA), with or without activation: LPS for MO culture and PHA for PBMC culture... (Complete abstract click electronic access below)
Keywords: Pulmões - Tuberculose - Aspectos imunológicos; Tuberculosis